Glandular Cells Atypia: Which Diagnosis? - Pisco, Filipa; Sousa, Nelson; Fonseca, Paula (Citotech Online - Case Review, 2016)
Ovarian cancer presents the highest mortality rate of all gynecological pathologies, since it is only diagnosed in an advanced stadium, when first symptoms appear. The study case represents a follow-up cytology, after a total hysterectomy for an undifferentiated ovary carcinoma. The cytological evaluation suggested an Adenocarcinoma, while the histological diagnosis of the nodular lesion revealed a relapse of Papillary Serous Ovarian Carcinoma. Performing the histological examination, in this and other cases, is a fundamental piece for the confirmation of the cytological diagnosis as well as for the differential diagnosis.